Pengaruh Budaya Organisasi dalam Meningkatkan Kinerja Karyawan di Era Digitalisasi pada CV DUTA BINTANG UTAMA - Jennie Rorensia; Iska Nadiyatus Sholihah; Eritawana Eritawana; Jesia Jesia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of organizational culture on improving employee performance in facing the digitalization era at CV DUTA BINTANG UTAMA. This company is a company engaged in computerization and security systems, including devices such as computers, laptops, CCTV, and others. This company also provides sales and repair services for devices. In addition, this company also acts as an official distributor and service center for several brands of computers, laptops, and printers. CV DUTA BINTANG UTAMA has a total of 34 employees. The research approach uses a descriptive qualitative method with data collection techniques through observation, interviews, documentation, and literature review. The results of the study indicate that the organizational culture implemented by the company, including customer focus, work ethics, discipline, innovation, and employee welfare, has a significant impact on individual and team performance. Although in general this culture supports work productivity and effectiveness, this organizational culture can have negative impacts if not carried out with a good strategy such as mental stress and lack of work flexibility that arise due to the implementation of a culture that is too strict or not adaptive to digital transformation, but the Company has found a strategy to overcome so that there is no negative impact from organizational culture. The implications of this study emphasize the importance of strategically adjusting organizational culture to align with technological developments, without neglecting the company's core values, so as to create an adaptive, innovative, and sustainable work environment.